Repeatability for yield total solids in a segregating population of rubber (Hevea brasiliensis) in Colombia (2018)
Rubber (Hevea brasiliensis) is a specie of late yield performance. This makes breeding programs long-term and the decisions taken are based in the base population genetic parameters. The aim ofthis research was to determinate a genetic potential of a rubber segregating population through the use of repeatability as a parameter, in order to make decisions to start a breeding program, with the purpose of increasing the total solids. In addition, to describe the target population and to explore the relation between total solids yield and climate variables. This research was carried out in a segregating population with 3395 trees in 12,000 m2 divided into nine plots located in the research center El Nus of Corpoica. Ten evaluations of total solids were recorded in the period between October 2014 and September 2016. The repeatability of total solids was determined from the estimation of individual and temporal environments variance using the Bayesian approach. Descriptive statistics for the total solid mean were used per plot and the correlation between total solids and climate variables were obtained.The repeatability estimate value was between 0.64 and 0.66. The plots had a total solids variation coefficient among 64.76 and 86.51%. Total solids and cumulate photosynthetic active radiation had a direct correlation (0.25) for 15 and 30 days prior period, while mean relative humidity had an inverse correlation of -0.44 and -0.42 with total solid in the same periods. There is a good probability that for this population the total solid can be inherited in a high proportion.